Efektivitas Teknik Self Management untuk Mereduksi Perilaku Maladaptif Siswa - Siti Erika Dahmayanti; Wikan Galuh Widyarto (Program Studi Bimbingan dan Konseling FKIP UMSU, 2022)
This study aims to test the effectiveness of self management techniques in reducing students' maladaptive behavior. The method used is quantitative with pre-experimental design type one group pre-test post-test design. Subject selection is done using purposive sampling method. This research was conducted in MTs Pakel Tulungagung. The population in this study was MTs Pakel Tulungagung students who numbered 31 students, while the sample in this study as many as 7 students who had high maladaptive behavior. The data analysis was conducted using paired sample t-test and hypothesis test using SPSS version 26 application. The results showed significant differences in student behavior changes provided by group guidance services with self management techniques. From the calculation of paired sample t-test obtained significance value (2-tailed) 0.000 0.05 which means Ha received and H0 rejected, meaning group guidance with self management techniques can reduce maladaptive behavior of students in MTs Pakel Tulungagung.